2019
DOI: 10.1158/1538-7445.panca19-c59
|View full text |Cite
|
Sign up to set email alerts
|

Abstract C59: NRF2 drives metabolic reprogramming in irradiated pancreatic cancer cells and promotes radioresistance

Abstract: The current 5-year survival rate of pancreatic ductal adenocarcinoma (PDAC) is ~8%. The dismal prognosis in PDAC reflects in part an exceptional level of resistance to available therapies. Approximately half of PDAC patients present with localized tumors amenable to local therapies, though only a minority are candidates for potentially curative surgery due to unresectable disease, which leaves radiation therapy (RT) as the only other option. The clinical reality is that two thirds of all PDAC patients succumb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The protective role of Nrf2 against cytotoxics-induced oxidative stress and apoptosis is well established [ 37 ]. Moreover, McDonald et al [ 38 ] and Bailleul et al [ 39 ] found that Nrf2 activation mediates radioresistance in mouse embryonic fibroblasts and human pancreatic cancer. Notably in our study, nuclear Nrf2 expression, as well as the transcriptional activity of Nrf2, was up-regulated in both radioresistant and parental TNBC cells in response to IR, implying a potential role of Nrf2 against IR-induced oxidative stress [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The protective role of Nrf2 against cytotoxics-induced oxidative stress and apoptosis is well established [ 37 ]. Moreover, McDonald et al [ 38 ] and Bailleul et al [ 39 ] found that Nrf2 activation mediates radioresistance in mouse embryonic fibroblasts and human pancreatic cancer. Notably in our study, nuclear Nrf2 expression, as well as the transcriptional activity of Nrf2, was up-regulated in both radioresistant and parental TNBC cells in response to IR, implying a potential role of Nrf2 against IR-induced oxidative stress [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally to metabolism reprogramming, NRF2 has been shown to promote proliferation, angiogenesis, resistance to apoptosis and, through the epithelial to mesenchymal transition (EMT) activation, metastasis [44]. More details are awaited; however, Bailleul et al did observe that NRF2 promotes radioresistance thanks to a powerful antioxidant response through metabolic reprogramming and pro-survival autophagy [45]. Autophagy is associated with either pro-survival or pro-death mechanisms depending on the circumstances [40,46].…”
Section: Mechanisms Of Resistancementioning
confidence: 99%